Energy Engineering Proceedings of CAETS 2015 Convocation on Pathways to Sustainability - Raghavan, K.V.; Ghosh, Purnendu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book contains the proceedings of CAETS 2015 Convocation on 'Pathways to Sustainability: Energy, Mobility and Healthcare Engineering' that was held on October 13-14, 2015 in New Delhi. This 3 volume proceedings provide an international forum for discussion and communication of engineering and technological issues of common concern. This volume talks about 'Energy' and includes 22 chapters on diverse topics like renewable energy, advances and applications of bio-energy and bio-refinery, energy options and scenarios, wind energy for buildings and transportation, etc. The contents of this volume will be useful to researchers, professionals, and policy makers alike.
Chapter 1. Low Carbon Pathways for India and the World -- Chapter 2. Fuel Cell Technologies for Defence Applications -- Chapter 3. Wind Energy for Buildings and Transport Sectors -- Chapter 4. Waste to Biohydrogen: Addressing Sustainability with Environmental Biorefinery -- Chapter 5. Indian Advances in Fast Breeder Nuclear Reactor Engineering -- Chapter 6. China's long road to the high-efficiency, clean, and low-carbon energy transition -- Chapter 7. The Possible Rate of Transition to Lower-carbon Housing -- Chapter 8. Solar Cells: Materials beyond Silicon -- Chapter 9. Nano-Bio-Photonics: Integrating Technologies to Meet Challenges in Energy, Mobility and Healthcare -- Chapter 10. Carbon Dioxide to Energy: Killing Two Birds with One Stone -- Chapter 11. Multi Scale Optimization of Building Energy -- Chapter 12. Emerging Construction Materials for Energy Infrastructure -- Chapter 13. Energy Efficient Power Generation and Water Management through Membrane Technology -- Chapter 14. Transition to Lower Carbon Energy Regime: Engineering Challenges in Building and Transportation Sectors -- Chapter 15. Energy Options and Scenarios for Transitioning to a Lower Carbon Economy: An Indian Perspective -- Chapter 16. Mixed Culture Chain Elongation (MCCE) - A Novel Biotechnology for Renewable Biochemical Production from Organic Residual Streams -- Chapter 17. Bio-Energy and Bio-Refinery: Advances and Applications -- Chapter 18. Sulfonated Polyethersulfone/Torlon Blend Membrane Incorporated with Multi-walled Carbon Nanotubes for Energy Production Using Microbial Fuel Cell -- Chapter 19. Development of Sulfonated Polyethersulfone/Matrimid Acid-Base Blend Membrane for Energy Production through Fuel Cells -- Chapter 20. Adaption of a Green Technology (Friction Stir Welding) to Join Fusion Energy Materials -- Chapter 21. Advanced Materials for Indian Future Nuclear Energy Systems -- Chapter 22. Mitigating Embrittlement in Structural Steels of Power Plants by Grain Boundary Engineering.
Keywords: Renewable energy sources; Energy policy; Energy and state; Electric power production; Renewable Energy; Energy Policy, Economics and Management; Electrical Power Engineering; Mechanical Power Engineering